Еnergy dependence of cross section of photonuclear reactions on indium isotopes - Zhaba, V.I.; Haysak, I.I.; Parlag, A.M.; Bohinyuk, V.S.; Lazorka, M.M. (Вопросы атомной науки и техники, 2018)
Experimental isomeric yield ratios for the ¹¹³Іn(γ,n)С¹¹²mgIn reactions on the betatron B25/30 bremsstrahlung
gamma beam of energy range 12…25 МеV are measured. Effective cross-sections of (γ,n)-reactions with ¹¹²mIn and
¹¹⁴mIn isomers output are calculated. The Penfold-Leiss and Tikhonov methods are applied to solve the Volterra integral equation. The obtained experimental cross-sections are compared with theoretical calculations using the
TALYS-1.6 code На гальмівному пучку бетатрона Б25/30 в області енергій 12…25 МеВ проведено вимірювання ізомерного відношення виходу реакції ¹¹³Іn(γ,n)¹¹²mgIn. За експериментальними значеннями енергетичних виходів
розраховано перерізи (γ,n)-реакції на ізотопах індію з утворенням ізомерів ¹¹²mIn і ¹¹⁴mIn. Для розрахунків
застосовано методи Пенфольда-Лейсса і Тіхонова. Отримані експериментальні дані порівнюються з теоретичними розрахунками в TALYS-1.6. На тормозном пучке бетатрона Б25/30 в области энергий 12…25 МэВ проведено измерение изомерного
отношения выхода реакции ¹¹³Іn(γ,n)¹¹²mgIn. По экспериментальным значениям энергетических выходов рассчитаны сечения (γ,n)-реакции на изотопах индия с образованием изомеров ¹¹²mIn и ¹¹⁴mIn. Для расчетов
применены методы Пенфольда-Лейсса и Тихонова. Полученные экспериментальные данные сравниваются с
теоретическими расчетами в TALYS-1.6.